Mechanistic modeling indicates rapid glyphosate dissipation and sorption‐driven persistence of its metabolite AMPA in soil. Issue 2 (17th January 2023) - Wimmer, Benedikt; Langarica‐Fuentes, Adrian; Schwarz, Erik; Kleindienst, Sara; Huhn, Carolin; Pagel, Holger
Abstract: Residual concentrations of glyphosate and its main transformation product aminomethylphosphonic acid (AMPA) are often observed in soils. The factors controlling their biodegradation are currently not well understood. We analyzed sorption‐limited biodegradation of glyphosate and AMPA in soil with a set of microcosm experiments. A mechanistic model that accounts for equilibrium and kinetic sorption facilitated interpretation of the experimental results. Both compounds showed a biphasic dissipation with an initial fast (up to Days 7–10) and subsequent slower transformation rate, pointing to sorption‐limited degradation. Glyphosate transformation was well described by considering only equilibrium sorption. Model simulations suggested that only 0.02–0.13% of total glyphosate was present in the soil solution and thus bioavailable. Glyphosate transformation was rapid in solution (time required for 50 % dissipation of the total initially added chemical [DT50 ] = 3.9 min), and, despite strong equilibrium sorption, total glyphosate in soil dissipated quickly (DT50  = 2.4 d). Aminomethylphosphonic acid dissipation kinetics could only be described when considering both equilibrium and kinetic sorption. In comparison to glyphosate, the model simulations showed that a higher proportion of total AMPA was dissolved and directly bioavailable (0.27–3.32%), but biodegradation of dissolved AMPA was slower (DT50  = 1.9 h). The model‐based data interpretation suggests that kinetic sorption strongly reduces AMPA bioavailability, leading to increased AMPA persistence in soil (DT50  = 12 d). Thus, strong sorption combined with rapid degradation points to low risks of glyphosate leaching by vertical transport through soil in the absence of preferential flow. Ecotoxicological effects on soil microorganisms might be reduced. In contrast, AMPA persists, rendering these risks more likely. Core Ideas: Mechanistic modeling indicated sorption‐limited biodegradation of glyphosate and AMPA. Biodegradation of glyphosate was faster (DT90 = 12 d) compared with AMPA (DT90 = 86 d). Equilibrium sorption limited glyphosate degradation, which was fast in solution (DT50 = 4 min). Kinetic sorption might trigger AMPA persistence. AMPA poses a higher risk of leaching and ecotoxicological effects than glyphosate.